Stereoselective reduction of chiral 2-furoic acid derivatives using group I metals in ammonia - Donohoe, T; Calabrese, A; Stevenson, C; Ladduwahetty, T (2000)
A series of chiral auxiliaries have been attached to 2-furoic acid and 3-methyl-2-furoic acid. The performance of these auxiliaries in the Birch reduction was assessed and it was found that placing a C-3 methyl group on the heterocycle was essential for good stereoselectivity. Using bis(methoxymethyl)pyrrolidine high levels of diastereoselectivity could be obtained with a range of electrophiles. A model is also presented which explains the sense of stereoselectivity displayed by this auxiliary. After reduction, the auxiliaries could be removed by reaction with acid to furnish dihydrofuran-based carboxylic acids with high enantiomeric excess. © The Royal Society of Chemistry 2000.